Non-suicidal Self-Injury (NSSI): The Influence of Adverse Childhood Experiences (ACEs) and Interpersonal Relationships in Early Adulthood - Hidayat, Muhamad Agam; Puri, Valendra Granitha Shandika; Adriani, Yufi; Luzvinda, Liany (Indonesian Psychological Research, 2026)
Non-suicidal self-injury (NSSI) is often adopted as a maladaptive coping mechanism to manage complex emotional stress. This study investigates the influence of Adverse Childhood Experiences (ACE), including childhood maltreatment, family/household dysfunction, and exposure to violence outside the home, and interpersonal functioning factors such as  avoidance of interpersonal intimacy,  disagreement, connection, conflict, emotional experience, and expressing emotions on the likelihood of engaging in NSSI. A quantitative research design was employed with a sample of 207 university students aged 18–25 years selected via accidental sampling. Data were collected using the Inventory of Statements About Self-Injury (ISAS), the WHO ACE-International Questionnaire (ACE-IQ), and the Functional Idiographic Assessment Template Questionnaire (FIAT-Q). Confirmatory factor analysis was conducted using LISREL 8.8, and multiple regression analysis was performed out using SPSS 26.0. The findings revealed that ACE and interpersonal relationship variables significantly predicted NSSI, accounting for 21.1% of the variance. Emotional experience and expressing emotions emerged as the strongest contributing factors. This finding suggests that individuals with intense emotional experience and heightened emotional expressiveness are more vulnerable to NSSI, thereby requiring for preventive psychoeducational interventions. Furthermore, the cognitive-behavioral therapy is recommended to support adaptive emotional regulation and reduce the risk of self-injury.